La bancarización como instrumento para la formalización laboral - Espinoza Castro, Lionel Adolfo (2024)
The high level of labor informality affecting Peru requires drastic and immediate solutions. Mandatory banking for the payment of labor economic benefits (hereinafter referred to as banking), implemented by the State along with other complementary policies, would allow for a short-term reduction in labor informality and, additionally, would improve the quality of life for millions of people, as well as enhance the fiscal revenue and treasury. The solution hinges on political decision-making, as these would be highly unpopular measures that are, nonetheless, necessary for the viability of the country.